Positive electrode material for lithium ion battery and preparation method of positive electrode material
Through carbon nanotimal surface carboxyl radiation treatment and burning temperature control, the lithium -ion battery positive material with a three -dimensional porous network structure is prepared, which solves the problem of insufficient conductivity and circulation stability, and achieves high -power performance and long life characteristics.
Patent Information
- Application Number
- CN202411975628.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The conductivity and lithium ion transmission rate of the existing lithium-ion battery positive electrode materials are low, resulting in serious electrode polarization and insufficient cycling stability and long-life characteristics.
Through the carbon -based carboxyl radiation treatment of the carbon nanotuba, prepare the front -pole material with a three -dimensional porous network structure, and to reasonably control the burning temperature through reasonable control to form a small metal oxide particles with a small particle size and evenly distributed.
It significantly improves the electrical, multiplier performance, and cycle stability of the material. The first discharge is higher than the capacity, and the Kuron efficiency can reach more than 95%. The capacity can remain above 95%.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a positive electrode material for a lithium ion battery and a preparation method thereof. Background Art
[0002] With the rapid growth of modern society's demand for portable electronic devices, electric vehicles and energy storage systems, lithium-ion batteries have become one of the most widely used secondary batteries due to their high energy density, long cycle life and excellent rate performance. However, in order to meet the application requirements of high energy density, high rate performance and long life, the performance improvement of lithium-ion battery cathode materials remains a research focus and difficulty.
[0003] At present, the research on positive electrode materials for lithium-ion batteries is mainly focused on improving their specific capacity, rate performance and cycle stability. In the preparation process of traditional positive electrode materials, the metal ion dispersion is poor, and after calcination, it is easy to form metal oxide particles with large particle size and uneven distribution, resulting in low conductivity and lithium ion transfer rate of the material, and severe electrode polarization, which limits the rate performance and cycle life of the battery. In addition, the positive electrode material is prone to volume changes and side reactions during the cycle process, further reducing the cycle stability and long life characteristics of the battery. Therefore, how to improve the microstructure and electrochemical properties of the positive electrode material by optimizing its composition and preparation process has become an important research direction in the current lithium-ion battery field. Summary of the invention
[0004] In view of this, the purpose of the present invention is to propose a positive electrode material for lithium-ion batteries and a preparation method thereof, so as to solve the problems of low conductivity and lithium ion transfer rate of existing positive electrode materials, severe electrode polarization, and insufficient cycle stability and long life characteristics due to volume changes and side reactions during the cycle.
[0005] Based on the above purpose, the present invention provides a positive electrode material for a lithium ion battery, which is obtained by calcining a positive electrode material precursor; the preparation method of the positive electrode material precursor is as follows: (1) treating carbon nanotubes with a mixed solution of sulfuric acid and nitric acid to obtain carboxylated carbon nanotubes; (2) adding carboxylated carbon nanotubes into deionized water, adjusting the pH to 8-8.5 with sodium hydroxide, freeze-drying, grinding and sieving to obtain carboxylated carbon nanotube aerogel powder; (3) Add polyvinyl alcohol, acrylic acid, and tripropylene glycol diacrylate to deionized water, stir for 20-40 minutes, then add lithium acetate dihydrate, nickel acetate tetrahydrate, manganese acetate tetrahydrate, cobalt acetate tetrahydrate, ammonium persulfate, and tetramethylethylenediamine, and continue stirring for 0.5-1.5 hours to obtain an impregnation solution; (4) Add the carboxylated carbon nanotube aerogel powder to the impregnation solution, ultrasonically disperse it for 20-40 minutes, heat it to 65-75°C, stir it for 2.5-3.5 hours, wash it with water, wash it with alcohol, and vacuum dry it to obtain a cathode material precursor.
[0006] Preferably, in step (1), the concentration of sulfuric acid is 98%, and the concentration of nitric acid is 65%.
[0007] Preferably, the volume ratio of sulfuric acid to nitric acid in the mixed solution of step (1) is 3:1.
[0008] Preferably, in step (1), the weight ratio of carbon nanotubes to the mixed solution is 1:8-12.
[0009] Preferably, the treatment time in step (1) is 0.5-1.5 h.
[0010] Preferably, in step (2), the weight ratio of carboxylated carbon nanotubes to deionized water is 1:4-6.
[0011] Preferably, the freeze-drying temperature in step (2) is -75±5°C and the time is 20-28h.
[0012] Preferably, in step (3), the weight ratio of polyvinyl alcohol, acrylic acid, tripropylene glycol diacrylate, deionized water, lithium acetate dihydrate, nickel acetate tetrahydrate, manganese acetate tetrahydrate and cobalt acetate tetrahydrate is 0.3-0.8:2-4:0.1-0.5:15-25:0.51-1.53:1-3:0.12-0.37:0.12-0.37.
[0013] Preferably, in step (4), the weight ratio of the carboxylated carbon nanotube aerogel powder to the impregnation solution is 0.5:15-25.
[0014] Furthermore, the present invention also provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps: placing a positive electrode material precursor in a muffle furnace, heating the temperature from room temperature to 450-550°C at a rate of 3-8°C / min, keeping the temperature for 10-14h, then heating the temperature from 450-550°C to 650-750°C, keeping the temperature for 0.5-1.5h, cooling the temperature to room temperature, grinding and sieving to obtain a positive electrode material for a lithium ion battery.
[0015] Beneficial effects of the present invention: The lithium-ion battery prepared by the positive electrode material provided by the present invention has a high first discharge specific capacity, and its coulombic efficiency can reach more than 95%. In terms of rate performance, the 10C discharge specific capacity can reach more than 90% of the 0.1C discharge specific capacity, showing excellent rate performance. At the same time, after 500 cycles, the discharge specific capacity can still be maintained at more than 95%, showing excellent cycle stability and long life characteristics.
[0016] The present invention significantly improves the dispersibility of metal ions in the positive electrode material precursor by carboxylating the surface of carbon nanotubes, and forms metal oxide particles with small particle size and uniform distribution after calcination, thereby improving the conductivity, rate performance and cycle stability of the material. Furthermore, the carboxylation carbon nanotube aerogel powder prepared by freeze drying constructs a three-dimensional porous network structure, enhances the dispersibility of the material and the stability of the microstructure, and significantly improves the electrochemical performance of the battery.
[0017] The present invention effectively improves the dispersibility of carboxylated carbon nanotube aerogel powder and the structural integrity of the positive electrode material through the cross-linked structure formed by tripropylene glycol diacrylate and acrylic acid, and the addition of polyvinyl alcohol, and further improves the cycle stability. Reasonable control of the calcination temperature avoids the decomposition of carbon nanotubes, ensuring the integrity of the framework structure of the positive electrode material and the stability of the conductive network. The positive electrode material prepared by the present invention is suitable for the field of lithium-ion batteries with high requirements for energy density, rate performance and cycle life, and has broad application prospects. DETAILED DESCRIPTION
[0018] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0019] In the specific implementation manner of the present invention, carbon nanotubes were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model C121257, inner diameter 2-5nm, outer diameter <8nm, length 10-30μm; the concentration of sulfuric acid was 98%; the concentration of nitric acid was 65%.
[0020] Embodiment 1: (1) 1 g of carbon nanotubes was added to a mixed solution of 8 g of sulfuric acid and nitric acid (volume ratio of 3:1), ultrasonicated for 0.5 h, washed with deionized water three times, and vacuum dried at 80 °C for 24 h to obtain carboxylated carbon nanotubes; (2) adding 1 g of carboxylated carbon nanotubes to 4 g of deionized water, adjusting the pH to 8.0 with sodium hydroxide, freeze-drying at -70 °C for 20 h, and grinding through a 200-mesh sieve to obtain carboxylated carbon nanotube aerogel powder; (3) Add 0.3 g of polyvinyl alcohol (PVA1788), 2 g of acrylic acid, and 0.1 g of tripropylene glycol diacrylate to 15 g of deionized water, stir for 20 min, then add 0.51 g of lithium acetate dihydrate, 1 g of nickel acetate tetrahydrate, 0.12 g of manganese acetate tetrahydrate, 0.12 g of cobalt acetate tetrahydrate, 35 mg of ammonium persulfate, and 25 mg of tetramethylethylenediamine, and continue stirring for 0.5 h to obtain an impregnation solution; (4) Add 0.5 g of carboxylated carbon nanotube aerogel powder to 15 g of impregnation solution, ultrasonically disperse for 20 min, then heat to 65 °C, stir for 2.5 h, wash with water, wash with alcohol, and finally vacuum dry at 80 °C for 24 h to obtain a cathode material precursor; (5) The cathode material precursor was placed in a muffle furnace, heated from room temperature to 450°C at a rate of 3°C / min, kept at this temperature for 10 h, then heated from 450°C to 650°C, kept at this temperature for 0.5 h, cooled, and ground through a 100-mesh sieve to obtain a cathode material for lithium-ion batteries.
[0021] Embodiment 2: (1) 1 g of carbon nanotubes was added to a mixed solution of 10 g of sulfuric acid and nitric acid (volume ratio of 3:1), ultrasonicated for 1 h, washed with deionized water for 3 times, and vacuum dried at 80 °C for 24 h to obtain carboxylated carbon nanotubes; (2) adding 1 g of carboxylated carbon nanotubes to 5 g of deionized water, adjusting the pH to 8.2 with sodium hydroxide, freeze-drying at -75 °C for 24 h, and grinding through a 200-mesh sieve to obtain carboxylated carbon nanotube aerogel powder; (3) Add 0.5 g polyvinyl alcohol (PVA1788), 3 g acrylic acid, and 0.3 g tripropylene glycol diacrylate to 20 g deionized water, stir for 30 min, then add 1.02 g lithium acetate dihydrate, 1.99 g nickel acetate tetrahydrate, 0.25 g manganese acetate tetrahydrate, 0.25 g cobalt acetate tetrahydrate, 40 mg ammonium persulfate, and 30 mg tetramethylethylenediamine, and continue stirring for 1 h to obtain an impregnation solution; (4) Add 0.5 g of carboxylated carbon nanotube aerogel powder to 20 g of impregnation solution, ultrasonically disperse for 30 min, then heat to 70 °C, stir for 3 h, wash with water, wash with alcohol, and finally vacuum dry at 80 °C for 24 h to obtain a cathode material precursor; (5) The cathode material precursor was placed in a muffle furnace, heated from room temperature to 500°C at a rate of 5°C / min, kept warm for 12 h, then heated from 500°C to 700°C, kept warm for 1 h, cooled, and ground through a 100-mesh sieve to obtain a cathode material for lithium-ion batteries.
[0022] Embodiment 3: (1) 1 g of carbon nanotubes was added to a mixed solution of 12 g of sulfuric acid and nitric acid (volume ratio of 3:1), ultrasonicated for 1.5 h, washed with deionized water three times, and vacuum dried at 80 °C for 24 h to obtain carboxylated carbon nanotubes; (2) adding 1 g of carboxylated carbon nanotubes to 6 g of deionized water, adjusting the pH to 8.5 with sodium hydroxide, freeze-drying at -80 °C for 28 h, and grinding through a 200-mesh sieve to obtain carboxylated carbon nanotube aerogel powder; (3) Add 0.8 g of polyvinyl alcohol (PVA1788), 4 g of acrylic acid, and 0.5 g of tripropylene glycol diacrylate to 25 g of deionized water, and stir for 40 min. Then add 1.53 g of lithium acetate dihydrate, 3 g of nickel acetate tetrahydrate, 0.37 g of manganese acetate tetrahydrate, 0.37 g of cobalt acetate tetrahydrate, 45 mg of ammonium persulfate, and 35 mg of tetramethylethylenediamine, and continue stirring for 1.5 h to obtain an impregnation solution. (4) Add 0.5 g of carboxylated carbon nanotube aerogel powder to 25 g of impregnation solution, ultrasonically disperse for 40 min, then heat to 75 °C, stir for 3.5 h, wash with water, wash with alcohol, and finally vacuum dry at 80 °C for 24 h to obtain a cathode material precursor; (5) The cathode material precursor was placed in a muffle furnace, heated from room temperature to 550°C at a rate of 8°C / min, kept at this temperature for 14 h, then heated from 550°C to 750°C, kept at this temperature for 1.5 h, cooled, and ground through a 100-mesh sieve to obtain a cathode material for lithium-ion batteries.
[0023] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the carboxylated carbon nanotubes in step (2) are replaced with carbon nanotubes; The specific steps are as follows: (1) 1 g of carbon nanotubes was added to 5 g of deionized water, and then the pH was adjusted to 8.2 with sodium hydroxide, and then freeze-dried at -75 °C for 24 h, and ground through a 200-mesh sieve to obtain carboxylated carbon nanotube aerogel powder; (2) Add 0.5 g of polyvinyl alcohol (PVA1788), 3 g of acrylic acid, and 0.3 g of tripropylene glycol diacrylate to 20 g of deionized water, stir for 30 min, then add 1.02 g of lithium acetate dihydrate, 1.99 g of nickel acetate tetrahydrate, 0.25 g of manganese acetate tetrahydrate, 0.25 g of cobalt acetate tetrahydrate, 40 mg of ammonium persulfate, and 30 mg of tetramethylethylenediamine, and continue stirring for 1 h to obtain an impregnation solution; (3) Add 0.5 g of carboxylated carbon nanotube aerogel powder to 20 g of impregnation solution, ultrasonically disperse for 30 min, then heat to 70 °C, stir for 3 h, wash with water, wash with alcohol, and finally vacuum dry at 80 °C for 24 h to obtain a cathode material precursor; (4) The cathode material precursor was placed in a muffle furnace, heated from room temperature to 500°C at a rate of 5°C / min, kept warm for 12 h, then heated from 500°C to 700°C, kept warm for 1 h, cooled, and ground through a 100-mesh sieve to obtain the cathode material.
[0024] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the carboxylated carbon nanotube aerogel powder in step (4) is replaced by carboxylated carbon nanotubes; The specific steps are as follows: (1) 1 g of carbon nanotubes was added to a mixed solution of 10 g of sulfuric acid and nitric acid (volume ratio of 3:1), ultrasonicated for 1 h, washed with deionized water for 3 times, and vacuum dried at 80 °C for 24 h to obtain carboxylated carbon nanotubes; (2) Add 0.5 g of polyvinyl alcohol (PVA1788), 3 g of acrylic acid, and 0.3 g of tripropylene glycol diacrylate to 20 g of deionized water, stir for 30 min, then add 1.02 g of lithium acetate dihydrate, 1.99 g of nickel acetate tetrahydrate, 0.25 g of manganese acetate tetrahydrate, 0.25 g of cobalt acetate tetrahydrate, 40 mg of ammonium persulfate, and 30 mg of tetramethylethylenediamine, and continue stirring for 1 h to obtain an impregnation solution; (3) Add 0.5 g of carboxylated carbon nanotubes to 20 g of the impregnation solution, disperse by ultrasonication for 30 min, heat to 70 °C, stir for 3 h, wash with water, wash with alcohol, and finally vacuum dry at 80 °C for 24 h to obtain a cathode material precursor; (4) The cathode material precursor was placed in a muffle furnace, heated from room temperature to 500°C at a rate of 5°C / min, kept warm for 12 h, then heated from 500°C to 700°C, kept warm for 1 h, cooled, and ground through a 100-mesh sieve to obtain the cathode material.
[0025] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that: tripropylene glycol diacrylate is not added in step (3); The specific steps are as follows: (1) 1 g of carbon nanotubes was added to a mixed solution of 10 g of sulfuric acid and nitric acid (volume ratio of 3:1), ultrasonicated for 1 h, washed with deionized water for 3 times, and vacuum dried at 80 °C for 24 h to obtain carboxylated carbon nanotubes; (2) adding 1 g of carboxylated carbon nanotubes to 5 g of deionized water, adjusting the pH to 8.2 with sodium hydroxide, freeze-drying at -75 °C for 24 h, and grinding through a 200-mesh sieve to obtain carboxylated carbon nanotube aerogel powder; (3) Add 0.5 g polyvinyl alcohol (PVA1788) and 3 g acrylic acid to 20 g deionized water, stir for 30 min, then add 1.02 g lithium acetate dihydrate, 1.99 g nickel acetate tetrahydrate, 0.25 g manganese acetate tetrahydrate, 0.25 g cobalt acetate tetrahydrate, 40 mg ammonium persulfate and 30 mg tetramethylethylenediamine, continue stirring for 1 h to obtain an impregnation solution; (4) Add 0.5 g of carboxylated carbon nanotube aerogel powder to 20 g of impregnation solution, ultrasonically disperse for 30 min, then heat to 70 °C, stir for 3 h, wash with water, wash with alcohol, and finally vacuum dry at 80 °C for 24 h to obtain a cathode material precursor; (5) The cathode material precursor was placed in a muffle furnace, heated from room temperature to 500°C at a rate of 5°C / min, kept warm for 12 h, then heated from 500°C to 700°C, kept warm for 1 h, cooled, and ground through a 100-mesh sieve to obtain the cathode material.
[0026] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that: polyvinyl alcohol is not added in step (3); The specific steps are as follows: (1) 1 g of carbon nanotubes was added to a mixed solution of 10 g of sulfuric acid and nitric acid (volume ratio of 3:1), ultrasonicated for 1 h, washed with deionized water for 3 times, and vacuum dried at 80 °C for 24 h to obtain carboxylated carbon nanotubes; (2) adding 1 g of carboxylated carbon nanotubes to 5 g of deionized water, adjusting the pH to 8.2 with sodium hydroxide, freeze-drying at -75 °C for 24 h, and grinding through a 200-mesh sieve to obtain carboxylated carbon nanotube aerogel powder; (3) Add 3 g of acrylic acid and 0.3 g of tripropylene glycol diacrylate to 20 g of deionized water, stir for 30 min, then add 1.02 g of lithium acetate dihydrate, 1.99 g of nickel acetate tetrahydrate, 0.25 g of manganese acetate tetrahydrate, 0.25 g of cobalt acetate tetrahydrate, 40 mg of ammonium persulfate and 30 mg of tetramethylethylenediamine, and continue stirring for 1 h to obtain an impregnation solution; (4) Add 0.5 g of carboxylated carbon nanotube aerogel powder to 20 g of impregnation solution, ultrasonically disperse for 30 min, then heat to 70 °C, stir for 3 h, wash with water, wash with alcohol, and finally vacuum dry at 80 °C for 24 h to obtain a cathode material precursor; (5) The cathode material precursor was placed in a muffle furnace, heated from room temperature to 500°C at a rate of 5°C / min, kept warm for 12 h, then heated from 500°C to 700°C, kept warm for 1 h, cooled, and ground through a 100-mesh sieve to obtain the cathode material.
[0027] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that: in step (5), the temperature is directly raised from room temperature to 700° C. and kept at this temperature for 13 h; The specific steps are as follows: (1) 1 g of carbon nanotubes was added to a mixed solution of 10 g of sulfuric acid and nitric acid (volume ratio of 3:1), ultrasonicated for 1 h, washed with deionized water for 3 times, and vacuum dried at 80 °C for 24 h to obtain carboxylated carbon nanotubes; (2) adding 1 g of carboxylated carbon nanotubes to 5 g of deionized water, adjusting the pH to 8.2 with sodium hydroxide, freeze-drying at -75 °C for 24 h, and grinding through a 200-mesh sieve to obtain carboxylated carbon nanotube aerogel powder; (3) Add 0.5 g polyvinyl alcohol (PVA1788), 3 g acrylic acid, and 0.3 g tripropylene glycol diacrylate to 20 g deionized water, stir for 30 min, then add 1.02 g lithium acetate dihydrate, 1.99 g nickel acetate tetrahydrate, 0.25 g manganese acetate tetrahydrate, 0.25 g cobalt acetate tetrahydrate, 40 mg ammonium persulfate, and 30 mg tetramethylethylenediamine, and continue stirring for 1 h to obtain an impregnation solution; (4) Add 0.5 g of carboxylated carbon nanotube aerogel powder to 20 g of impregnation solution, ultrasonically disperse for 30 min, then heat to 70 °C, stir for 3 h, wash with water, wash with alcohol, and finally vacuum dry at 80 °C for 24 h to obtain a cathode material precursor; (5) The cathode material precursor was placed in a muffle furnace, heated from room temperature to 700°C at a rate of 5°C / min, kept at this temperature for 13 h, cooled, and ground through a 100-mesh sieve to obtain a cathode material for a lithium-ion battery.
[0028] Battery preparation: Positive electrode sheet: The positive electrode materials prepared in the embodiment and the comparative example are respectively used as active materials, acetylene black is used as a conductive agent, and a 1-methyl-2-pyrrolidone solution of 4% by mass of polyvinylidene fluoride is used as a binder. The positive electrode active material, 4% PVDF, and acetylene black are weighed in a mass ratio of 75:15:10 and mixed evenly. The mixture is stirred for 6 hours at room temperature. The obtained slurry is evenly coated on a clean aluminum foil, and vacuum dried at 60°C overnight to remove the organic solvent. The positive electrode sheet is then punched with a punching machine having a punch diameter of 12 mm to obtain a positive electrode sheet. Battery assembly: The positive electrode sheet obtained above is used as the positive electrode, the lithium sheet is used as the negative electrode, the electrolyte is a 1M LiPF6 organic solution, the solvent composition is dimethyl carbonate / diethyl carbonate / ethylene carbonate (volume ratio is 1:1:1), the diaphragm is a polypropylene film, and the assembled battery model is a 2032 button cell. The battery assembly order is positive electrode shell, positive electrode sheet, diaphragm, negative electrode sheet, negative electrode shell, a total of 6 drops of electrolyte are added, and then the battery is packaged with a battery packaging machine. The packaged battery is left to stand for 12 hours and the performance test is carried out.
[0029] Performance Test: Constant current charge and discharge test: The Xinwei battery testing system was used to test the charge and discharge specific capacity, cycle performance and rate performance of the batteries prepared from the positive electrode materials of the embodiments and comparative examples. The charge and discharge specific capacity at room temperature was measured using a current of 0.1C, and the cycle performance at room temperature was measured using a current of 1C. The rate performance test range was 0.1C, 0.2C, 0.5C, 1C and 2C, 5 cycles each, and the voltage test range was 2.0-4.75V. The results are shown in Table 1.
[0030] Table 1 Performance test results
[0031] Data Analysis: From the data of Examples 1-3 in Table 1, it can be seen that the lithium-ion battery prepared by the positive electrode material for lithium-ion batteries provided by the present invention has a high first discharge specific capacity, and its coulombic efficiency can reach more than 95%. In addition, in the rate test, the discharge specific capacity at 10C can reach more than 90% of the discharge specific capacity at 0.1C, indicating that it has excellent rate performance. Most importantly, after 500 cycles, its discharge specific capacity can still be maintained at more than 95, indicating that it has excellent cycle stability and long life characteristics. This shows that the positive electrode material of the present invention can still maintain excellent electrochemical properties under high rate charge and discharge conditions, and is suitable for lithium-ion battery application scenarios with high requirements for energy density, rate performance and cycle life.
[0032] From the data of Example 2 and Comparative Example 1 in Table 1, it can be seen that the carboxylation of the surface of carbon nanotubes can effectively improve the coulombic efficiency, rate performance and cycle stability of the battery. This is mainly because the carboxylation of the surface of carbon nanotubes helps to assist acrylic acid in improving the dispersion of metal ions in the positive electrode material precursor, thereby forming smaller particles and uniformly dispersed metal oxides during the later calcination process, thereby significantly improving the microstructure and electrochemical properties of the positive electrode material. Smaller and evenly distributed metal oxide particles can effectively improve the conductivity and lithium ion transfer rate of the material, reduce electrode polarization, and improve rate performance. At the same time, the uniform particle distribution and stable structure can reduce volume changes and side reactions during the cycle, thereby significantly improving the cycle stability and long life characteristics of the battery.
[0033] It can be seen from the data of Example 2 and Comparative Example 2 that, compared with the direct use of carboxylated carbon nanotubes, the carboxylated carbon nanotube aerogel powder formed after freeze-drying can effectively improve the coulombic efficiency, rate performance and cycle stability of the battery, which is mainly attributed to the freeze-drying treatment to construct a three-dimensional porous network structure between the carboxylated carbon nanotubes. This structure effectively enhances the dispersibility of metal ions in the positive electrode material precursor and promotes the formation of more uniform and stable metal oxide particles during the subsequent calcination process. In addition, the three-dimensional porous network structure significantly improves the conductivity and lithium ion transfer rate of the positive electrode material, reduces the electrode polarization, and thus significantly improves the rate performance. At the same time, the network structure can buffer the volume change of the material during the battery cycle, inhibit the occurrence of side reactions, and further improve the cycle stability and long life characteristics of the battery. This structural optimization provides an important guarantee for the electrochemical properties of the positive electrode material.
[0034] It can be seen from the data of Example 2 and Comparative Example 3 that the addition of tripropylene glycol diacrylate can improve the cycle stability of the battery, which is mainly attributed to the cross-linked structure formed by tripropylene glycol diacrylate and acrylic acid, which helps to enhance the dispersibility of carboxylated carbon nanotube aerogel powder in the positive electrode material precursor, thereby forming a more uniform and stable positive electrode material microstructure after calcination. This cross-linked structure not only improves the mechanical strength and structural integrity of the positive electrode material, but also effectively alleviates the volume change of the material during the cycle and reduces the occurrence of side reactions. In addition, the uniform and stable microstructure can improve the transmission efficiency of lithium ions and the conductivity of the electrode, thereby further improving the cycle stability and long life characteristics of the battery.
[0035] It can be seen from the data of Example 2 and Comparative Example 4 that the addition of polyvinyl alcohol can improve the cycle stability of the battery, which is mainly because polyvinyl alcohol helps to promote the dispersibility of carboxylated carbon nanotube aerogel powder in the positive electrode material precursor.
[0036] It can be seen from the data of Example 2 and Comparative Example 5 that directly raising the temperature to 700°C during the later calcination process will lead to a decrease in the coulombic efficiency, rate performance and cycle stability of the battery. This is mainly because long-term calcination at high temperature may cause the decomposition or loss of some carbon nanotubes, thereby destroying the integrity and stability of the framework structure of the positive electrode material. The loss of carbon nanotubes will cause the conductive network of the positive electrode material to be destroyed, the lithium ion transmission path to be blocked, and then increase the electrode polarization and reduce the rate performance. In addition, the decreased stability of the framework structure will also lead to an increase in the volume change of the material during the cycle and an increase in side reactions, thereby significantly reducing the cycle stability and long life characteristics of the battery.
[0037] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A positive electrode material for a lithium ion battery, characterized in that: The positive electrode material precursor is obtained by calcining; the preparation method of the positive electrode material precursor is as follows: (1) treating carbon nanotubes with a mixed solution of sulfuric acid and nitric acid to obtain carboxylated carbon nanotubes; (2) adding carboxylated carbon nanotubes into deionized water, adjusting the pH to 8-8.5 with sodium hydroxide, freeze-drying, grinding and sieving to obtain carboxylated carbon nanotube aerogel powder; (3) Add polyvinyl alcohol, acrylic acid, and tripropylene glycol diacrylate to deionized water, stir for 20-40 minutes, then add lithium acetate dihydrate, nickel acetate tetrahydrate, manganese acetate tetrahydrate, cobalt acetate tetrahydrate, ammonium persulfate, and tetramethylethylenediamine, and continue stirring for 0.5-1.5 hours to obtain an impregnation solution; (4) Adding the carboxylated carbon nanotube aerogel powder to the impregnation solution, ultrasonically dispersing for 20-40 min, heating to 65-75 ° C, stirring for 2.5-3.5 h, washing with water, washing with alcohol, and vacuum drying to obtain a cathode material precursor; In step (1), the concentration of sulfuric acid is 98%, and the concentration of nitric acid is 65%; In the step (3), the weight ratio of polyvinyl alcohol, acrylic acid, tripropylene glycol diacrylate, deionized water, lithium acetate dihydrate, nickel acetate tetrahydrate, manganese acetate tetrahydrate and cobalt acetate tetrahydrate is 0.3-0.8:2-4:0.1-0.5:15-25:0.51-1.53:1-3:0.12-0.37:0.12-0.37; In the step (4), the weight ratio of the carboxylated carbon nanotube aerogel powder to the impregnation solution is 0.5:15-25.
2. The positive electrode material for lithium ion battery according to claim 1, characterized in that The volume ratio of sulfuric acid to nitric acid in the mixed solution of step (1) is 3:
1.
3. The positive electrode material for lithium ion battery according to claim 1, characterized in that In the step (1), the weight ratio of the carbon nanotubes to the mixed solution is 1:8-12.
4. The positive electrode material for lithium ion battery according to claim 1, characterized in that The treatment time in step (1) is 0.5-1.5h.
5. The positive electrode material for lithium ion battery according to claim 1, characterized in that In the step (2), the weight ratio of the carboxylated carbon nanotubes to deionized water is 1:4-6.
6. The positive electrode material for lithium ion battery according to claim 1, characterized in that The freeze-drying temperature in step (2) is -75±5°C and the time is 20-28h.
7. A method for preparing a positive electrode material for a lithium ion battery according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: placing a positive electrode material precursor into a muffle furnace, first heating the temperature from room temperature to 450-550°C at a rate of 3-8°C / min, keeping the temperature for 10-14h, then heating the temperature from 450-550°C to 650-750°C, keeping the temperature for 0.5-1.5h, cooling the temperature to room temperature, grinding and sieving, and obtaining a positive electrode material for lithium-ion batteries.
Citation Information
Patent Citations
Preparation method for Ni-Co / carbon nanotube aerogel catalyst of zinc-air battery
CN105609790A
Preparation method of lithium ion battery positive electrode material and lithium ion battery positive electrode material prepared by employing method
CN107316994A
Flexible self-supporting positive electrode material, preparation method thereof and application thereof
CN111668453A
Doped and coated composite modified lithium nickel manganese oxide positive electrode material and preparation method thereof
CN116404168A
Cross-Linked Carbon Nanotube Networks
US20140012034A1